A STUDY ON GRAMMATICAL ERRORS IN WRITING DESCRIPTIVE TEXT MADE BY THE FIRST YEAR STUDENTS OF SMP ISLAM AS-SHOFA PEKANBARU - Cerli Marsita; Rumiri Aruan; Jismulatif Jismulatif (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is aimed to find out the types of grammatical errors in writing descriptive text made by the first year students of SMP Islam As-Shofa Pekanbaru. This is quantitative descriptive research. The population of this research were the first year students of SMP Islam As-Shofa Pekanbaru. The sample of this research was 25 students of 7.5 class who have been selected using cluster-sampling technique. The data were collected by using writing test 1 and writing test 2. The data were analyzed by applying the rules of Corder (1974) through three raters. The findings of this study revealed that the students made 190 grammatical errors from the total frequency of writing test 1 and writing test 2. Those grammatical errors were classified into four types which belong to Surface Strategy Taxonomy, they are omission (28%), addition (13%), misformation (48%), and misordering (11%). The cause of errors are the presence of intralingual transfer and interlingual transfer. Based on the findings, there were several recommendations given to the students to minimize the errors that will occur such as improve their skills in writing English with do more practice to write a text and understand to the grammar used.Key Words: Error, Writing, Desciptive Text